The Influence of Trading Activity in Price Discovery of Reissued Bonds in Sub-National Bond Markets in India - Parmar, Chandra Kant; Ghosh, Abhinab (International Journal of Economics and Financial Issues, 2025)
This study investigates the pricing determinants of reissued Indian state government bonds (State Development Loans), focusing on the influence of secondary market dynamics. Analysing a panel of 36 unique bonds across 163 reissue events, it explores how past market behavior shapes outcomes in the primary auction market. The research employs a dynamic panel data model using the Arellano-Bond Generalized Method of Moments (GMM) estimator, effectively addressing endogeneity and bond-specific unobserved effects. Key independent variables include the volume-weighted average price (VWAP), trading volume from the secondary market, bond maturity, and macroeconomic controls such as the policy repo rate. Findings reveal that secondary market VWAP and trading volume significantly impact reissue pricing, while the repo rate plays a limited role. Notably, in 78.5% of reissues, bonds are priced below their secondary market VWAP, with an average discount of −0.58, reflecting investor yield expectations in light of fixed coupon structures. These insights have important implications for public debt management, suggesting that secondary market sentiment drives primary market pricing. While central bond price discovery is well-studied, this paper uniquely addresses the neglected area of reissue pricing at the subnational level, offering valuable empirical evidence on auction dynamics and market efficiency in India’s state bond markets.